Towards greater understanding of implementation during systematic reviews of complex healthcare interventions: the framework for implementation transferability applicability reporting (FITAR) - Baxter, Susan (BMC Med Res Methodol, 2019)
BACKGROUND: There have been calls for greater consideration of applicability and transferability in systematic reviews, to improve their usefulness in informing policy and practice. Understanding how evidence is, or is not applicable and transferable to varying local situations and contexts, is a key challenge for systematic review synthesis in healthcare. Assessing applicability and transferability in systematic reviews is reported to be difficult, particularly in reviews of complex interventions. There is a need for exploration of factors perceived to be important by policy-makers, and for further guidance on which items should be reported. In this paper we focus on the process of development of a framework that can be used by systematic reviewers to identify and report data across studies relating to applicability and transferability. METHODS: The framework was developed by scrutinising existing literature on applicability and transferability, examining data during a systematic review of highly complex changes to health service delivery, and was informed by stakeholder engagement. The items of the framework were thus grounded in both data identified during a real review, and stakeholder input. The paper describes examples of data identified using the framework during a review of integrated care interventions, and outlines how it informed analysis and reporting of the review findings. RESULTS: The Framework for Implementation Transferability Applicability Reporting (FITAR) comprises 44 items which can be used to structure analysis and reporting across studies during systematic reviews of complex interventions. The framework prompts detailed consideration of contextual data during extraction and reporting, within areas of: patient type and populations; type of organisations and systems; financial and commissioning processes; systems leadership elements; features of services; features of the workforce; and finally elements of the interventions/initiatives. CONCLUSIONS: Use of the framework during our review of complex healthcare interventions helped the review team to surface contextual data, which may not be commonly extracted, analysed and reported. Further exploration and evaluation of systems for identifying and reporting these factors during reviews is required. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12874-019-0723-y) contains supplementary material, which is available to authorized users.